Brainy Puzzles

Puzzle Solvers: Interesting brainy puzzles shared by fellow puzzlers

301 Members

Join this group to post and comment.

# Puzzlefor you all!!!!

So here comes a new puzzle for everyone....

you have to use the mathematical operators in between the numbers to get the correct output....

1 1 1 =6

2 2 2 =6

3 3 3 =6

4 4 4 =6

5 5 5 =6

6 6 6 =6

7 7 7 =6

8 8 8 =6

9 9 9 =6

its very simple ,you all can easily solve it....

you have to use the mathematical operators in between the numbers to get the correct output....

1 1 1 =6

2 2 2 =6

3 3 3 =6

4 4 4 =6

5 5 5 =6

6 6 6 =6

7 7 7 =6

8 8 8 =6

9 9 9 =6

its very simple ,you all can easily solve it....

(1+1+1)! = 6

2+2+2 = 6

3x3-3 = 6

4+4-(sqrt 4) = 6 [positive square root]

(5/5)+5 = 6

6-6+6 = 6

7-(7/7) = 6

- bah -

(squrt 9) x (sqrt 9) - (sqrt 9) =6

2+2+2 = 6

3x3-3 = 6

4+4-(sqrt 4) = 6 [positive square root]

(5/5)+5 = 6

6-6+6 = 6

7-(7/7) = 6

- bah -

(squrt 9) x (sqrt 9) - (sqrt 9) =6

I hope to answer the 8,

8-sqrt(8/(cube root(8))) = 6

8-sqrt(8/(cube root(8))) = 6

If I were not bored, I'd do -mahulI hope to answer the 8,

8-sqrt(8/(cube root(8))) = 6

cuberoot (8) + cuberoot (8) + cuberoot (8) = 6 😁

Wow! that's a lot better.... 😀

wow...

such quick replies..

CE rocks!!!!

such quick replies..

CE rocks!!!!

Ayan, take this as yet-another warning. Further spamming will lead to banning. If you want to make test posts, go here -

CE - Newbie Training Center - CrazyEngineers Forum

of course, instead of posting 'jdfsdlks...', try posting something that makes sense.

CE - Newbie Training Center - CrazyEngineers Forum

of course, instead of posting 'jdfsdlks...', try posting something that makes sense.

devesh,i think i am so late but..,

(1!+1!+1!)! =6

2+ 2+ 2 =6

3 *3- 3 =6

4 +4-sqrt(4) =6

(5/5)+ 5 =6

6 +6- 6 =6

7-(7/7) =6

cuberoot(8)+cuberoot(8)+cuberoot(8) =6

sqrt(9)*sqrt(9) -sqrt(9)=6

(1!+1!+1!)! =6

2+ 2+ 2 =6

3 *3- 3 =6

4 +4-sqrt(4) =6

(5/5)+ 5 =6

6 +6- 6 =6

7-(7/7) =6

cuberoot(8)+cuberoot(8)+cuberoot(8) =6

sqrt(9)*sqrt(9) -sqrt(9)=6

Prashanth_p@cchi, thank you..